PESAN-PESAN EDUKATIF TGK. MUHAMMAD DAUD BEUREUEH - Mahmud Saleh (Universitas Islam Negeri Ar-Raniry, 2016)
Tgk. Muhammad Daud Beureueh was one of the leaders of Aceh who had a great contribution in developing Acehnese civilization. Besides known as an Islamic scholar, he was also known as a key person who developed education in Aceh. His educational ideas were not merely to educate young people to become academic community, but have political goals to provoke them to become a pioneer of the independence. Through the establishment of educational institutions, he propagated the idea of rebellion against Dutch colonialism. Keywords: